Research in an intercultural context: mediator-investigators of epidemiological health studies, bridges between two worlds - Alcouffe, Leslie; Tareau, Marc-Alexandre; Oberlis, Margot; Adenis, Antoine; Vignier, Nicolas (Frontiers in Public Health, 2024)
Context French Guiana is a French overseas department where very different linguistic, cultural and societal populations live together in a small area. Health issues and their specific epidemiological profiles call for research projects crossing several cultures. In this context, health mediators have a role to play in research. The aim of this study was to describe the perceptions, attitudes and opinions on research of mediators and researchers collaborating on research projects, and to describe the strengths and difficulties encountered during this cooperation. Methods The Inter-med project was conducted in French Guiana between February 2022 and April 2023 on the base of semi-directive interviews with mediators, or researchers, all working in health research in the intercultural context of French Guiana. The socio-demographic characteristics of the participants were described. An inductive thematic analysis was carried out on all the interviews, and word occurrence analysis on certain themes. The information was triangulated with field coordination notebooks from two epidemiological surveys conducted in French Guiana between 2021 and 2022. Results A total of 26 semi-structured interviews were conducted and 1,328 notebook pages analyzed. Mediation was described as an indispensable interface between the world of research and that of the population targeted by a survey. Mediators have a role to play at different stages of projects, in respect of good clinical practice, ethics and legislation. They act as interfaces between languages, concepts and representations. Their profession remains under-defined and under-dimensioned. The jobs offered are often precarious. Mediation work is emotionally costly, calls on soft skills and requires a combination of rigor and flexibility. All these aspects are implemented in the specific world of research, where there are common concepts and divergent perceptions. Researchers and mediators converge on a common goal: improving health. Conclusion This study covers several aspects of the development and implementation of research projects. Respect for good clinical practice and people, transparency and data quality are redundant concerns, and this study touches on ethnocentrism, stigmatization and cultural representations. This study points out that the integration and recognition of mediators could be beneficial in research conducted in a cross-cultural context.